Respuesta :
Answer:
[tex]x=5,\frac{-9+\sqrt{255}i }{4} ,\frac{-9-\sqrt{255}i }{4}[/tex]
Step-by-step explanation:
1) Move all terms to one side.
[tex]2x^{3} -x^{2} -3x-210=0[/tex]
2) Factor [tex]2{x}^{3}-{x}^{2}-3x-210[/tex] using Polynomial Division.
1 - Factor the following.
[tex]2x^{3} -x^{2} -3x-210[/tex]
2 - First, find all factors of the constant term 210.
[tex]1,2,3,4,5,6,7,10,14,15,21,30,35,42,70,105,210[/tex]
3) Try each factor above using the Remainder Theorem.
Substitute 1 into x. Since the result is not 0, x-1 is not a factor..
[tex]2*1^{3} -1^{2} -3*1-210=-212[/tex]
Substitute -1 into x. Since the result is not 0, x+1 is not a factor..
[tex]2(-1)^{3} -(-1)^{2} -3*-1-210=-210[/tex]
Substitute 2 into x. Since the result is not 0, x-2 is not a factor..
[tex]2*2^{3} -2^{2} -3*2-210=-204[/tex]
Substitute -2 into x. Since the result is not 0, x+2 is not a factor..
[tex]2{(-2)}^{3}-{(-2)}^{2}-3\times -2-210 = -224[/tex]
Substitute 3 into x. Since the result is not 0, x-3 is not a factor..
[tex]2\times {3}^{3}-{3}^{2}-3\times 3-210 = -174[/tex]
Substitute -3 into x. Since the result is not 0, x+3 is not a factor..
[tex]2{(-3)}^{3}-{(-3)}^{2}-3\times -3-210 = -264[/tex]
Substitute 5 into x. Since the result is 0, x-5 is a factor..
[tex]2\times {5}^{3}-{5}^{2}-3\times 5-210 =0[/tex]
------------------------------------------------------------------------------------------
⇒ [tex]x-5[/tex]
4) Polynomial Division: Divide [tex]2{x}^{3}-{x}^{2}-3x-210[/tex] by [tex]x-5[/tex].
[tex]2x^{2}[/tex] [tex]9x[/tex] [tex]42[/tex]
-------------------------------------------------------------------------
[tex]x-5[/tex] | [tex]2x^{3}[/tex] [tex]-x^{2}[/tex] [tex]-3x[/tex] [tex]-210[/tex]
[tex]2x^{3}[/tex] [tex]-10x^{2}[/tex]
-----------------------------------------------------------------------
[tex]9x^{2}[/tex] [tex]-3x[/tex] [tex]-210[/tex]
--------------------------------------------------------------------------
[tex]42x[/tex] [tex]-210[/tex]
[tex]42x[/tex] [tex]-210[/tex]
-------------------------------------------------------------------------
5) Rewrite the expression using the above.
[tex]2x^2+9x+42[/tex]
[tex](2x^2+9x+42)(x-5)=0[/tex]
3) Solve for [tex]x.[/tex]
[tex]x=5[/tex]
4) Use the Quadratic Formula.
1 - In general, given [tex]a{x}^{2}+bx+c=0[/tex] , there exists two solutions where:
[tex]x=\frac{-b+\sqrt{b^{2} -4ac} }{2a} ,\frac{-b-\sqrt{b^2-4ac} }{2a}[/tex]
2 - In this case, [tex]a=2,b=9[/tex] and [tex]c = 42.[/tex]
[tex]x=\frac{-9+\sqrt{9^2*-4*2*42} }{2*2} ,\frac{-9-\sqrt{9^2-4*2*42} }{2*2}[/tex]
3 - Simplify.
[tex]x=\frac{-9+\sqrt{255}i }{4} ,\frac{-9-\sqrt{255}i }{4}[/tex]
5) Collect all solutions from the previous steps.
[tex]x=5,\frac{-9+\sqrt{255}i }{4} ,\frac{-9-\sqrt{255}i }{4}[/tex]